HUBUNGAN PENGETAHUAN DAN SIKAP IBU TERHADAP PENGGUNAANKB METODE KONTRASEPSI JANGKA PANJANG (MKJP) DI WILAYAH KERJA PUSKESMAS PARAMASAN KABUPATEN BANJAR, MARTAPURA - Ari Widyarni; Siska Dhewi (Journal of Midwifery and Reproduction, 2018)
Long-term contraception method (MKJP) is a type of contraception that is very effective for avoiding births, regulating birth intervals and not affecting sexual relations that can last for 3 years to a lifetime such as IUD, Implants, MOW and MOP. Long-term contraceptive methods (MKJP) have proven to be the most effective way to reduce pregnancy rates, but until now MKJP has not yet become the choice of the majority of couples of reproductive age in Indonesia. Kabupaten Banjar, Martapura are still included in the regions where the coverage of MKJP KB is low, it can be seen in the achievement figures which show a significant decrease in 2015 reached 6.6%, in year 2016 reached 7.0% and in year 2017, only 2.3%. This research is a quantitative study with a cross sectional approach. The population and sample are mothers with criteria for women of childbearing age (WUS) as family planning acceptors who visit and seek treatment at Puskesmas Paramasan Kabupaten Banjar. A large sample of 60respondents. Data was collected by interview using a structured questionnaire, the results of data collection were analyzed using univariate and bivariate statistics with a chi square test using a computer program with a significance value (α)≤0.05. The results of the univariate analysis showed that the majority of respondents did not use MKJP KB, most of the respondents had sufficient knowledge and most respondents' attitudes were sufficient. Bivariate analysis showed that there was a correlation between knowledge of the use of MKJP KB (p-value =0.001) and there was a relationship between attitudes towards the use of MKJP KB (p-value =0.000).It is recommended for agencies to be concerned about the need for cross-sector cooperation in an effort to increase respondents' knowledge and attitudes about the advantages and disadvantages of using MKJP KB.It is expected that with the increased knowledge held by respondents about MKJP KB, then the attitude of respondents in contraceptive use for KB MKJP is expected to be better.And will affect the increase in the number of MKJP KB use.